The Relationship between Cerebral Infarction and Angiographic Characteristics in Childhood Moyamoya Disease - Mugikura, Shunji; Takahashi, Shoki; Higano, Shuichi; Shirane, Reizo; Kurihara, Noriko; Furuta, Susumu; Ezura, Masayuki; Takahashi, Akira (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: In childhood-onset moyamoya disease, the angiographic disease process of stenoocclusive lesions is progressive, and cerebral infarctions often develop as a result of ischemia. Our purpose was to determine how the severity of stenoocclusive lesions in the anterior and posterior circulations affects the distribution of cerebral infarction in patients with childhood-onset moyamoya disease.METHODS: In 69 patients with childhood-onset moyamoya disease, angiograms were reviewed for stenoocclusive lesions, and CT scans, MR images, or both were reviewed for the sites and extent of cerebral infarction. The relationship between the angiographic and CT/MR findings was examined.RESULTS: The prevalence and degree of stenoocclusive lesions of the posterior cerebral artery (PCA) significantly correlated with the extent of lesions around the terminal portion of the internal carotid artery (ICA). The prevalence of infarction significantly correlated with the degree of stenoocclusive changes of both the ICA and PCA. Infarctions tended to be distributed in the anterior borderzone in less-advanced cases, while in more advanced cases lesions were additionally found posteriorly in the territory of the middle cerebral artery, the posterior borderzone, and the PCA territory.CONCLUSION: Our results indicate that progressive changes of the anterior and posterior circulations are associated with the distribution of cerebral infarction, culminating in a patchily disseminated or honeycomb pattern of infarction on CT and MR studies in late stages of the disease.